Effectiveness of Catharanthus roseus L. extract gel on TNF-α and IL-1β in the healing process of oral lesions - Dewi, Tri Purnami; Canisca Putri, Ni Putu Ayu Mas Mitha; Mertayasa, Dewa Kadek (Majalah Kedokteran Gigi Indonesia, 2025)
The global incidence of oral lesions ranges from 5% to 66%, with an average of 20%. To date, no scientific research has investigated the effects of Catharanthus roseus L. (tapak dara) leaf extract on the expression of proinflammatory cytokines in oral lesion healing. This study aimed to evaluate the effectiveness of tapak dara leaf extract gel in reducing the expression of the proinflammatory cytokines TNF-α and IL-1β during oral lesion healing. A total of 30 mice (Mus musculus) were divided into five groups: four treatment groups and one control group, each housed separately. The gel formulation was prepared by mixing diluted extract solutions (5%, 10%, and 20%) into a 2% CMC-Na solution, heated and stirred for 10 minutes, and then cooled to achieve a gel consistency. Phytochemical screening was performed to qualitatively identify flavonoids, tannins, saponins, phenolics, alkaloids, steroids, and terpenoids. Expression levels of TNF-α and IL-1β were measured using an ELISA kit. ANOVA results showed that tapak dara leaf extract gel at 5%, 10%, and 20% significantly reduced TNF-α and IL-1β expression (p = 0.001). Tukey’s post hoc test indicated that the positive control (K+) group had the lowest expression of both TNF-α and IL-1β compared to other groups (p = 0.001). In conclusion, tapak dara leaf extract gel effectively reduces TNF-α and IL-1β expression, supporting its potential role in the healing process of oral lesions.